Big Data - Santos, Maribel Yasmina (River Publishers series in information science and technology., 2020)
This book addresses models and methods for designing and implementing Big Data Systems to support mixed and complexdecision processes, giving special attention to Big Data Warehouses as a way ofefficiently storing and processing batch or streaming data for structured orsemi-structured analytical problems.